Sij Davidove zvezde na sončni strani Alp - Podbersič, Renato (Studia Historica Slovenica, 2022)
On the basis of accessible archival sources and literature, the paper attempts to show the activities of the small number of Jews in Slovenia after the Second World War. After the Holocaust and the emigration, mainly to Israel, the remaining Jews in Slovenia organized themselves within the framework of the Jewish community in Ljubljana, which was part of a wider Yugoslav union with its center in Belgrade. Except for individuals who did not emphasize their Jewishness, they generally did not enter Slovenian everyday life. Their activity revived after the independence of Slovenia in 1991, but even today our country remains the only one in the EU without a rabbi living permanently on its territory.
Keywords: Jews; Judaism; Judje; Judovstvo; Sinagoge; Slovenia; Synagogues; Švarc, Mladen A.; Yugoslavia